NanR Regulates Sporulation and Enterotoxin Production by Clostridium perfringens Type F Strain F4969 - Mi, Eric (Infect Immun, 2018)
Clostridium perfringens type F strains, which produce C. perfringens enterotoxin (CPE), are a major cause of gastrointestinal infections, including the second most prevalent bacterial foodborne illness and 5 to 10% cases of antibiotic-associated diarrhea. Virulence of type F strains is primarily ascribable to CPE, which is synthesized only during sporulation. Many type F strains also produce NanI sialidase and carry a nan operon that likely facilitates uptake and metabolism of sialic acid liberated from glycoconjugates by NanI. During vegetative growth of type F strain F4969, NanR can regulate expression of nanI. Given their importance for type F disease, the current study investigated whether NanR can also influence sporulation and CPE production when F4969 or isogenic derivatives are cultured in modified Duncan-Strong sporulation (MDS) medium. An isogenic F4969 nanR null mutant displayed much less sporulation and CPE production but more NanI production than wild-type F4969, indicating that NanR positively regulates sporulation and CPE production but represses NanI production in MDS. Results for the nanR mutant also demonstrated that NanR regulates expression of the nan operon. A nanI nanR double null mutant mirrored the outcome of the nanR null mutant strain but with a stronger inhibition of sporulation and CPE production, even after overnight incubation. Coupled with results using a nanI null mutant, which had no impairment of sporulation or CPE production, NanR appears to carefully modulate the availability of NanI, nan operon-encoded proteins and sialic acid to provide sufficient nutrients to sustain sporulation and CPE production when F4969 is cultured in MDS medium.